The Role Of Trust in Mediating Perceived Risk and Electronic Word-Of-Mouth Variables Against Repurchase Intention - Haya Nur Safa’atin; Heri Pratikto; Titis Shinta Dhewi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Customer loyalty can provide consumer satisfaction and pleasure, so it has an impact on repurchasing interest. This study aims to determine the direct and indirect effects of perceived risk and electronic word of mouth (E-WOM) on repurchase intention and trust in TikTok Shop consumers of Y and Z generations. This research uses a quantitative method with a descriptive explanatory type that explains the relationship between variables X, Y, and Z. Data collection techniques using purposive sampling and simple random sampling totaling 239 respondents. Data analysis in the research is a) descriptive analysis, b) SEM-PLS, and c) mediation test. The results showed: 1) Perceived risk has a positive effect on trust 2) Electronic word of mouth (E-WOM) has a positive effect on trust 3) Perceived risk harms repurchase intention 4) Electronic word of mouth (E-WOM) harms repurchase intention positively effect 5) Trust has a positive effect on repurchase intention 6) Perceived risk has a positive effect on repurchase intention through trust 7) E-WOM has a positive effect on repurchase intention through trust.